2019
DOI: 10.18535/ijsrm/v7i10.em05
|View full text |Cite
|
Sign up to set email alerts
|

Green Purchase Behavior: the Predictive Roles of Consumer Self-Determination, Perceived Customer Effectiveness and Perceived Price

Abstract: The overarching aim of this research is to empirically test the effect of customers’ self-determined needs on perceived customer effectiveness and green purchase behavior while assessing the moderating role of price. To achieve this aim, data is collected from 453 consumers in South Korea. The various hypotheses developed to achieve this aim are tested via the structural equations modeling technique. The results of the study reveal that autonomy, competence, and relatedness positively and significantly affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
(61 reference statements)
1
9
0
2
Order By: Relevance
“…The significant positive relationship between competence and halal food purchase intention led to the acceptance of H2 , which posits that consumers’ competence has a positive influence on their purchase intention of halal food products. The results are consistent with the findings of Amenuvor et al (2019) that competence is positively related to purchase intention of green purchase behavior. As competence is related to knowledge and the ability to perform a task, it is inferred that the enhanced knowledge and the ability to recognize halal food offerings in the market result in an increased purchase intention of halal food products.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The significant positive relationship between competence and halal food purchase intention led to the acceptance of H2 , which posits that consumers’ competence has a positive influence on their purchase intention of halal food products. The results are consistent with the findings of Amenuvor et al (2019) that competence is positively related to purchase intention of green purchase behavior. As competence is related to knowledge and the ability to perform a task, it is inferred that the enhanced knowledge and the ability to recognize halal food offerings in the market result in an increased purchase intention of halal food products.…”
Section: Discussionsupporting
confidence: 91%
“…Gilal et al (2019) argued that consumers' need for competence may have a strong effect on their purchase behavior. Amenuvor et al (2019) identified a significant effect of competence on green purchase behavior. Moreover, researchers have found a positive effect of halal knowledge on purchase intention (Awan et al, 2015).…”
Section: Competencementioning
confidence: 99%
See 1 more Smart Citation
“…3.4 Customer-directed problem-solving behavior, customer-directed opportunism and relationship continuity Wang et al (2012) identified customer-directed problem-solving behavior in their study as a critical partnering strategy in which salespeople develop and provide customers with valueadded solutions, minimize perceived risk, build confidence and eventually increase customer satisfaction and loyalty. A positive relationship between customer-directed sales behavior and customer behavioral results has been identified by literature (Morgan et al, 2009;Anderson et al, 1994;Amenuvor et al, 2019). Some scholars have argued that customerdirected problem-solving behavior (CDPSB) may cause opportunistic behaviors despite these positive outcomes.…”
Section: Impact Of Formal Salesforce Control Systemsmentioning
confidence: 99%
“…This includes, but is not limited to, hiding or deliberately distorting details, pushing products with higher profit margins or commission rates (even if other products are comparatively better for the customer) and applying undue sales pressure. Customers who sense these behaviors may lose faith or feel unhappy, which may ultimately lead to a relationship breakup (Roman and Ruiz, 2005;Amenuvor et al, 2019). Besides, customer-directed sales practices substantially affect customers' expectations about the brand, its goods and services, and their buying and behavioral intentions.…”
Section: Impact Of Formal Salesforce Control Systemsmentioning
confidence: 99%